Implementation of Grade Level Assessment Tool in Social Sciences (GLAT-SS) for Grade VI of Karnataka State Education Board - Vijetha, Palnaty; Upadhyay, Alok Kumar; Abbur, Anil (JOURNAL OF INDIAN EDUCATION, 2022)
This study attempted to implement Grade Level Assessment Tool Social Sciences (GLAT-SS) for Grade VI of the Karnataka State Education board. A total of 615 students participated in the study, 310 students were from the Kannada medium, and 305 students were from English medium schools. A convenient sampling technique was used to select the students across six districts in Karnataka state (including pilot study). Investigators employed a survey research design. The study was conducted in two major stages: Compilation of GLAT-SS test items and field testing of GLAT-SS. Kruskal-Wallis one way ANOVA test and Mann-Whitney-U test were used for the analysis of data. The results revealed a significant influence of different districts on students’ performance on GLAT-SS. However, there was no significant influence of the medium of instruction on students’ performance on GLAT-SS. A significant difference was also found in English medium and Kannada medium students’ performance across different districts of Karnataka state. As part of the study, the range of scores for GLAT-SS was determined in three levels: below average, average, and above average. The study highlights that GLAT-SS can identify students’ present performance levels for Grade VI in Social Sciences subject and accordingly help in planning the remedial teaching sessions.